Laser ablation - Accelerator mass spectrometry: An approach for rapid radiocarbon analyses of carbonate archives at high spatial resolution - Welte, Caroline; Fohlmeister, Jens (Analytical chemistry, 2016)
A new instrumental setup, combining laser ablation (LA) with accelerator mass spectrometry (AMS), has been investigated for the online radiocarbon (14C) analysis of carbonate records. Samples were placed in an in-house designed LA-cell, and CO2 gas was produced by ablation using a 193 nm ArF excimer laser. The 14C/12C abundance ratio of the gas was then analyzed by gas ion source AMS. This configuration allows flexible and time-resolved acquisition of 14C profiles in contrast to conventional measurements, where only the bulk composition of discrete samples can be obtained. Three different measurement modes, i.e. discrete layer analysis, survey scans, and precision scans, were investigated and compared using a stalagmite sample and, subsequently, applied to terrestrial and marine carbonates. Depending on the measurement mode, a precision of typically 1-5% combined with a spatial resolution of 100 μm can be obtained. Prominent 14C features, such as the atomic bomb 14C peak, can be resolved by scanning several cm of a sample within 1 h. Stalagmite, deep-sea coral, and mollusk shell samples yielded comparable signal intensities, which again were comparable to those of conventional gas measurements. The novel LA-AMS setup allowed rapid scans on a variety of sample materials with high spatial resolution.